The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/iub.2230
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA colorectal neoplasia differentially expressed alleviates sepsis‐induced liver injury via regulating miR‐126‐5p

Abstract: In this study, we intended to determine the detailed function and mechanism of long noncoding RNA (lncRNA) colorectal neoplasia differentially expressed (CRNDE) in liver injury induced by sepsis. Cecal ligation and perforation (CLP) models were adopted to induce sepsis in vivo with rats, and hepatic epithelial cells L02 were treated with lipopolysaccharide (LPS) to mimic sepsis in vitro. Enzyme‐linked immunosorbent assay was conducted to detect the levels of tumor necrosis factor (TNF‐α), interleukin‐6 (IL‐6),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…In our study, it also showed that the proportion of Th17 and Treg subsets changed significantly in sepsis and the differentiation of Th17 and Treg subsets could be regulated by the expression level of miR-126 in lymphocytes of septic rats. A study on septic rats has shown that upregulation of miR-126 by transfection could heighten the apoptosis of liver epithelial cells, which proved that miR-126 could improve liver injury in sepsis [35]. Another study on burn tissues and endothelial cells has shown that the upregulation of miR-126 could inhibit the apoptosis of endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it also showed that the proportion of Th17 and Treg subsets changed significantly in sepsis and the differentiation of Th17 and Treg subsets could be regulated by the expression level of miR-126 in lymphocytes of septic rats. A study on septic rats has shown that upregulation of miR-126 by transfection could heighten the apoptosis of liver epithelial cells, which proved that miR-126 could improve liver injury in sepsis [35]. Another study on burn tissues and endothelial cells has shown that the upregulation of miR-126 could inhibit the apoptosis of endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-identi ed that multiple lncRNAs are involved in the development of sepsis-induced liver injury. For example, lncRNA colorectal neoplasia, differentially displayed, relieves sepsis-caused liver damage by targeting miR-126-5p [28]. Circulating lncRNA NEAT1 is correlated with an unfavorable prognosis, high severity, and increased risk in sepsis patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies in LPS-induced macrophages showed that lncRNA NEAT1 interacted with Let-7a, targeting TLR4 that in turn contributed to the LPS-induced inflammatory response ( Zhang and Niu, 2019 ). Another lncRNA, which functions via ceRNA mechanism, lncRNA CRNDE overexpression in rats ameliorated sepsis-induced liver injury by inhibiting hepatic epithelial cell apoptosis through binding to miR-126-5p, and in turn promoting the expression of BCL2L2 ( Li et al., 2020 ).…”
Section: Role Of Lncrnas In Sepsis-induced Organ Dysfunctionsmentioning
confidence: 99%